Structural basis of synaptic vesicle assembly promoted by α-synuclein - Giuliana Fusco (Nature Portfolio, 2016)
α-synuclein, a protein associated to Parkinson's disease, is involved in synaptic vesicle interaction and assembly. Here, the authors use NMR spectroscopy and super-resolution microscopy to unveil the nature and molecular mechanism of α-synuclein-mediated synaptic vesicle clustering.